Do randomised clinical trials on dental caries adopt Open Science practices? - Acosta, Carolina de Picoli; Cenci, Jaisson; Brondani, Bruna; Elagami, Rokaia Ahmed; Pereira-Cenci, Tatiana; Cenci, Maximiliano Sergio; Huysmans, Marie-Charlotte D. N. J. M.; Raggio, Daniela Prócida; Braga, Mariana Minatel; Mendes, Fausto Medeiros (BMC Oral Health, 2024)
Background: Open Science Practices (OSPs) are essential when assessing research integrity and quality of Randomised Clinical Trials (RCTs). As dental caries represents a significant oral health burden, our objective was to identify and analyse the adoption of OSPs within RCTs focused on addressing this disease. Methods: We searched PubMed to retrieve RCTs related to dental caries published from January 2000 to March 2022. Two independent researchers assessed a random sample of these articles to evaluate their eligibility until reaching the minimum sample size. Then, the same examiners reviewed the included texts regarding the OSPs adopted in the articles. The collected variables related to OSPs were reporting guidelines, protocol registration, detailed methodology available, open-source software, statistical analysis code sharing, statistical analysis plan, data sharing, open peer review, and open access. Association analyses using logistic regression were conducted considering the publication year, the continent of the first author, impact factor and open-access policy of the journals (explanatory variables), and adoption of at least one OSP or one OSP other than open access (outcomes). The recommendations for adopting OSPs were assessed by reviewing the "Instructions for Authors" section of the most frequently used journals where the included papers were published. Results: 64.8% of the articles (95% Confidence Interval = 59.3–70.1%) adopted at least one OSP. However, no individual OSP was adopted by more than 50% of the articles. The most adopted practices were protocol registration (37.1%), the use of reporting guidelines (33.1%) and publishing open access (37.3%). These are also the OSPs most often recommended by journals in the Instructions for Authors. A few articles adopted other practices. Older articles presented a lower frequency of adopting these practices, and articles published in higher impact factor journals were positively associated with both outcomes. Conclusion: The RCTs published on dental caries demonstrate a low frequency of adoption of most OSPs. However, a trend toward increased adoption of these practices has been notable in recent years.